Clinical aspects and diagnosis of erythema migrans and borrelial lymphocytoma - Müllegger, R... R. (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2001)
There are three distinct cutaneous manifestations of Lyme borreliosis (LB), erythema migrans (EM), borrelial lymphocytoma (BL), and acrodermatitis chronica atrophicans. EM, the hallmark of early LB, is the most frequent manifestation of LB and develops within 4-180 days (median, 14 days) after an infectious tick bite. There are five different clinical types of EM. Solitary macular and solitary annular EM comprise more than 80% of all EM lesions. Lessfrequent variants are the bulls eye type, the minimal size EM, the combined BL and EM, and the multilocular EM. EM in children is most frequentlylocated in the head-neck region and often displays an atypical morphology. It may be associated with an ipsilateral peripheral facial palsy. Extracutaneous, usually mild and transient, signs and symptoms occur in up to 40% of all EM patients (major form of EM). They must not be confused with features of human granulocytic ehrlichiosis that is found in about 20% of LB patients in Austria. The diagnosis of EM is primarily made on clinical grounds. Serologic test results are often false negative or positive. Histopathology from lesional skin is a helpful adjunct to the diagnosis. Direct detection of B. burgdorferi (DNA) by cultivation or PCR can prove the diagnosis. BL is a subacute cutaneous manifestation of LB that has been defined as a stage 2 (early disseminated infection) manifestation, but may-also occur during early localized infection. It usually represents a solitary lesion in stereotypical locations (ear, nipple) and represents a B cell pseudolymphoma.
Keywords: Borrelia burgdorferi; Diagnosis; Epidemiology; Eritem kronični, migracijski; Erythema chronicum migrans; Lyme disease; Lymska bolezen sin Lymska borelioza; Pseudolymphoma; Psevdolimfom; Transmission